Hans Jonas: responsabilità ed eccesso - Sità, Michele (Verbum – Analecta Neolatina, 2003)
Nowadays, scientific progress seems to have reached such high levels that it can satisfy almost every human demand: mankind apparently has an absolute, unlimited, and sometimes irresponsible power at its disposal. As an opposition to the excesses of a technological civilization, Hans Jonas proposes an ethics based on responsibility, a kind of ’imperative’ which puts the arrogance of a thoughtless progress to a halt. The consequences and the impacts of human activity have by now become unforeseeable, and man may well lose control of his technological successes by turning them into real failures, not only for himself but potentially for all of humanity. Man’s responsibility must therefore depend not only on his own and his peers’ life, but also, maybe above all, on the life of the next generations. Man needs to look at not only the immediate present but also at the perspectives in the long run: he should begin to think in the long term and thus needs to rediscover himself. The elaboration of a theory of responsibility is therefore focuses on that rediscovery, a recovery of the truest authenticity, and the wish for a better future.